A qualitative case study on productive zakat and pentahelix-based empowerment: Insights from BAZNAS Malang Regency - Minarni, Minarni; Slamet, Slamet; Munir, Misbahul (Universitas Islam Indonesia, 2025)
IntroductionIn Indonesia, zakat is a critical Islamic social finance instrument aimed at poverty alleviation and community empowerment. While most zakat programs remain consumptive, the shift toward productive zakat offers a sustainable approach to improving economic welfare. However, empirical studies that examine its actual implementation and governance models are still scarce, particularly within the context of local zakat institutions in Indonesia.ObjectivesThis study investigates the implementation of productive zakat empowerment in Malang Regency by analyzing the role of the Pentahelix collaboration model—integrating government, academia, private sector, media, and community—in supporting the distribution and impact of zakat-based economic empowerment programs.MethodThis research adopts a qualitative case study design, focusing on BAZNAS Malang Regency as the unit of analysis. Data were collected through in-depth interviews with institutional stakeholders and triangulated with documentary analysis of zakat distribution reports from 2020 to 2024. The study utilizes an inductive analytical framework to examine how Pentahelix-based collaboration influences the effectiveness of productive zakat implementation.ResultsThe findings reveal that BAZNAS Malang Regency has made substantial progress in transitioning from consumptive to productive zakat programs through initiatives such as small-business capital provision and equipment distribution. These efforts, implemented across 33 subdistricts, have led to significant economic improvements for mustahiq, with an estimated 25% increase in income levels. Moreover, the study finds that the success of these programs is closely linked to multi-sector collaboration under the Pentahelix model, although disparities in stakeholder engagement and the absence of formal mentoring and evaluation frameworks remain.ImplicationsThe results highlight the potential of productive zakat as a tool for sustainable poverty alleviation and economic inclusion when combined with collaborative governance. The Pentahelix model provides a viable framework for institutionalizing such efforts, though further development is needed to ensure strategic alignment, measurable impact, and long-term sustainability.Originality/NoveltyThis study contributes to the growing literature on Islamic social finance by offering an in-depth case analysis of productive zakat practices supported by multi-stakeholder collaboration in Indonesia. It introduces a nuanced understanding of how zakat institutions can serve as developmental agents in achieving Islamic economic objectives beyond traditional charity models.